الحماية الجزائية للشاهد في القانون الجزائري - أحمد بومعزة, نبيلة (جامعة الوادي University of Eloued, 2019)
الملخص تعد شهادة الشهود من أهم وسائل الاثبات في المحاكمات الجزائية ،لأنها تؤثر تأثيرا كبيرا في مصير المحاكمات حيث يكون لها دور حاسم في ادانة المتهم أو تبرئته ، لذلك تمثل حماية الشهود أحد الأهداف الرئيسية للسياسة الجنائية المعاصرة و،ولذلك سعى المشرع الجزائري الى توفير الحماية اللازمة للشهود من خلال توفير الحماية الموضوعية في ظل قانون العقوبات و قانون الفساد و الحماية الاجرائية من خلال اصدار الأمر 15-02 المعدل و المتمم لقانون الاجراءات الجزائية الذي أضاف الفصل السادس الى الباب الثاني من الكتاب الأول تحت عنوان " حماية الشهود و الخبراء و الضحايا " والذي أقر حماية الشهود من الاعتداءات و التهديدات التي قد يتعرضون لها بهدف تشجيعهم على الادلاء بالشهادة . Abstract Witness testimony is one of the most important means of proof in criminal trials because it has a significant impact on the fate of trials where they have a decisive role in convicting or acquitting the accused. Witness protection is thus one of the main objectives of contemporary criminal policy. Therefore, the Algerian legislator sought to provide the necessary protection for witnesses through the provision of substantive protection under the Penal Code and the Law on Corruption and Procedural Protection through the issuance of the amended and supplemental Order 15-02 of the Code of Criminal Procedure, which added Chapter 6 to Part Two of the first book entitled " Protection of Witnesses, Experts and Victims ", which approved the protection of witnesses from attacks and threats they may face in order to encourage them to testify.
Keywords: الشاهد ; الحماية الجزائية ; تدابير الحماية; witness،Penal Protection،Protection measures